Implementasi Manajemen Konflik Pekerjaan-Keluarga, Konflik Keluarga-Pekerjaan, dan Stres Kerja yang Berpengaruh terhadap Kepuasan Karyawan PT Langgang Buana Perkasa - Nurlaila Nurlaila (Society, 2020)
This research aims to analyze the management of work-family conflict, family-work conflict, job stress, and its implementation that affect employee satisfaction of PT Langgang Buana Perkasa. Work and family are two important spheres in an adult’s social life. The need will not be met if unemployed. Today, a profession is also a mirror of self-actualization. Without family, individuals will feel alone and there is no place to give love. PT Langgang Buana Perkasa is a company engaged in ground handling services and transportation services on several airlines, which is located at Sultan Babullah airport, Ternate, North Maluku Province, Indonesia. This research used a qualitative descriptive method. Data were obtained through in-depth interviews and questionnaires. Literature and documentation studies are carried out to collect secondary data related to the object of research, including employees of PT Langgang Buana Perkasa, flight schedules, and PT Langgang Buana Perkasa. The data sources were selected using a purposive sampling technique. The results showed that (1) There are three characteristics of work-family conflict. Based on these three characteristics, it indicates that most employees experience conflict in work-family, but it does not affect job satisfaction; (2) There are five characteristics of family-work conflicts but employees still apply professionalism. This indicates that there is no direct conflict but it can trigger stress due to family demands on religious holidays and public holidays; (3) Physical exhaustion can lead to conflict when faced with family demands regarding that role.